EQUATION OF FLYWHEEL MOVEMENT IN AMORTIZED GIMBAL AND THEIR ANALYSIS - Tsidylo, I. V.; Mykhaylyuk, I. R. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
The article examines the transport system with flywheel engine, which is increasingly used in technology. It is an ecologically clean energy source with a high specific power. It is reliable and durable. The mechanical system occupies an intermediate place between the gyroscope and the flywheel, which rotates in rigidly fixed supports. It is necessary to conduct the row of researches on vibrofirmness for creation of such mechanical systems, to estimate them dynamic properties and to give out recommendations on creation of transport vehicles with the inertia stores of energy. Dependences of system kinetic and potential energy changes, Rayleigh function was brought by researchers. Damping of supports resilient elements was taken into account. Equalizations of the mechanical system motion were gotten. The analysis of fly-wheel motion was conducted and influence of equalizations nonlinear members on firmness of the mechanical system is conducted. The change of fly-wheel motion frequencies with depending on the parameters of the mechanical system was certain and its fitness for the practical use was appraised. Dependences of vibrations frequencies changes on the angulator of fly-wheel were gotten. It was set that frequency of nutation at the increase of angulator of fly-wheel grows, and frequency of recession diminishes. Frequency of nutation with the increase of resilient elements inflexibility of supports grows also and the oscillations of the flywheel and the parameters of the mechanical system are interrelated.